PEDAGOGICAL STRATEGIES FOR ENHANCING EMERGENT WRITING SKILLS AMONG PRE-PRIMARY SCHOOL PUPILS - ODEWUMI; Ruth Morenike (Indonesian Journal of Education (INJOE), 2026)
Emergent writing is a foundational aspect of early literacy that begins with children’s initial attempts at symbolic representation and progresses through developmental stages toward conventional writing. This examined pedagogical strategies for enhancing emergent writing skills among pre-primary school pupils. A descriptive survey design was adopted, involving 100 pre-primary school teachers selected from ten schools. Data were collected using a validated questionnaire (TPEQ) with a reliability coefficient of 0.81. Findings revealed that while teachers actively supported activities such as scribbling, phonetic spelling, and the use of instructional materials, there were notable gaps in creating consistent writing opportunities, providing guided interaction, and fostering positive teaching attitudes. Pedagogical practices such as demonstration, use of diverse materials, and play-based approaches significantly contributed to pupils’ writing development. However, limited emphasis on interactive and child-centered strategies constrained optimal outcomes. The study concludes that effective teacher roles, attitudes, and pedagogical methods are critical in promoting emergent writing skills. It recommends continuous teacher training, improved classroom environments, integration of play-based learning, and provision of adequate instructional materials to enhance early writing development.